Vibration analysis of functionally graded material (FGM) double layered floating raft structure by the spectro-geometric method. (February 2023) - He, Dongze; Wang, Qingshan; Zhong, Rui; Qin, Bin
Abstract: This paper aims to analyze the vibration characteristics of functionally graded material (FGM) double layered floating raft structures under various boundary conditions. The artificial virtual spring technique is introduced to simulate the boundary conditions and coupling effect between the FGM plates by adjusting the spring stiffness. The spectro-geometric method is used to describe the displacement admissible function, which overcomes the discontinuity or jump phenomenon at the boundary for the conventional Fourier series. Based on the unified Rayleigh-Ritz energy framework, the dynamic equations of the FGM double layered floating raft structure are derived, and the corresponding vibration characteristics are obtained. The correctness of the presented method is verified by some numerical examples of comparisons with the calculation results obtained from the finite element method. After that, parametric analysis is carried out to investigate the effects of material parameters, geometric parameters, coupling spring stiffness, and coupling damping on the steady-state response of the FGM double layered floating raft with various boundary conditions.